Metal influence on the iso- and hetero-selectivity of complexes of bipyrrolidine derived salan ligands for the polymerisation of rac-lactide1. Issue 8 (14th August 2015) - Jones, Matthew D.; Brady, Lauren; McKeown, Paul; Buchard, Antoine; Schäfer, Pascal M.; Thomas, Lynne H.; Mahon, Mary F.; Woodman, Timothy J.; Lowe, John P.
<x xml:space="preserve">Abstract</x> A series complexes based on 2, 2′-bipyrrolidine based salan ligands have been prepared and either isotactic or heterotactic PLA have been prepared.